Microbiological Surveillance of Heater-Cooler Units Used in Cardiothoracic Surgery for Detection of Mycobacterium chimaera - Schlotthauer, Uwe; Hennemann, Kai; Gärtner, Barbara C.; Schäfers, Hans-Joachim; Becker, Sören L. (The Thoracic and Cardiovascular Surgeon, 2022)
Mycobacterium chimaera is a nontuberculous mycobacterium that was identified as causative agent in a global outbreak of severe infections following open-chest cardiothoracic surgery. Heater-cooler units (HCUs), which were contaminated during the manufacturing process, were elucidated as the origin of this outbreak. Regular surveillance of water-containing HCUs used for cardiac surgery was recommended as one preventive measure. We present data on the occurrence of M. chimaera and other mycobacterial pathogens in different HCUs from one surgical center in Germany over a 42-month period. Water samples and swabs from seven different HCUs were taken between 2015 and 2018, and mycobacteria were detected in 50.6% (78/154) of water samples and 21.1% (4/19) of swabs. M. chimaera accounted for the majority of detected pathogens (77/83 isolates in water samples), but other species such as Mycobacterium gordonae were also found. Despite strict adherence to an intensified, regular disinfection procedure, the majority of HCUs remained positive for mycobacteria until the end of the study. In conclusion, additional measures are needed to reduce the risk of intraoperative transmission of M. chimaera, and our observations underscore the inherent infections risks associated with water-containing medical devices.
Keywords: aerosol; atypical mycobacteria; microbiology; infection; infection prevention; Mycobacterium chimaera